Effects of macrophytes on lake‐water quality across latitudes: a meta‐analysis. Issue 4 (17th December 2018) - Song, Yiluan; Liew, Jia Huan; Sim, Darren Z. H.; Mowe, Maxine A. D.; Mitrovic, Simon M.; Tan, Hugh T. W.; Yeo, Darren C. J.
Abstract : Macrophytes are widely recognized for improving water quality and stabilizing the desirable clear‐water state in lakes. The positive effects of macrophytes on water quality have been noted to be weaker in the (sub)tropics compared to those of temperate regions. We conducted a global meta‐analysis using 47 studies that met our set criteria to assess the overall effects of macrophytes on water quality (measured by phytoplankton chlorophyll a concentration, total nitrogen concentration, total phosphorus concentration, Secchi depth and the trophic state index) and to investigate how these effects correlate with latitude using meta‐regressions. We also examined if the effects of macrophytes on lake‐water quality differ with growth form and study design in (sub)tropical and temperate areas by grouping the data and then comparing the effect sizes. We found that macrophytes significantly reduced phytoplankton chlorophyll a concentration, total nitrogen concentration, total phosphorus concentration, as well as the trophic state index, but they did not have a significant overall effect on Secchi depth. The effects of macrophytes on reducing phytoplankton chlorophyll a concentration, total nitrogen concentration and the trophic state index did not differ with latitude. However, the reduction of total phosphorus concentration was greater at lower latitudes. We showed that at lower latitudes, the positive effects of macrophytes on water quality are similar to or greater than those at higher latitudes, thus challenging the prevailing paradigm of macrophytes being less effective at enhancing lake‐water quality in the (sub)tropics. Furthermore, our data showed that the macrophyte effects vary by growth forms, and the growth forms that positively affect water quality differ between the (sub)tropical and temperate areas. We showed a lack of significant macrophyte effects in surveys within and outside macrophyte stands, suggesting difference in the sensitivities of study designs or possibly weaker effects of macrophytes in lakes compared to experimental settings.